Potential Investor Claims and Possible State Defences During the Covid-19 Emergency - Sefriani Sefriani; Seguito Monteiro (Faculty of Law, Sriwijaya University, Indonesia, 2021)
Since it was announced as a public health emergency of international concern in 2019, Covid-19 has caused enormous loss of property and life. The country's emergency policies in responding to the Covid outbreak are numerous, such as closing public transportation and prohibiting the export of medical devices. These policies have potentially harmed the interests of investors. This study has three purposes: investors' potential claims to challenge state measures addressed to Covid-19, the legal defences of states, and the possibility of an international investment dispute. This study shows that investors' potential claims may be delivered based on violations of the principles of fair and equal treatment, full protection and security, and national treatment and the most favoured nations. While a state can defend itself based on the principles of force majeure and state necessity, states can also defence through Non preclude measures or right to regulate clause in international investment agreements. In addition, it would also be better to build international solidarity and cooperation to mitigate and defeat the Covid-19 pandemic than sue the government before ISDS. States need collective action to avoid a surge of investor-state Arbitration. Governments’ policy to combat Covid-19 is to be considered as acting in necessity and therefore cannot be found in breach of their investment treaty obligations as long as that policy meet the necessity, proportionate, and non-discrimination requirements.